WATERSHED DELINEATION USING DIGITAL ELEVATION MODEL IN ARCGIS (PANGEEA, 2025)
The watersheds can be useful in defining the boundaries of the basin or to divide that basin into subbasins. This case study aims to create a boundary that represents the contributing area for a certain pour point. The watershed is delineated from the DEM (Digital Elevation Model) by calculating flow direction and flow accumulation and using them further into the analysis. To achieve this, ArcGIS will be used to perform the analysis leading to watershed delineation.
Keywords: watershed delineation; GIS; DEM; flow direction; flow accumulation